SURFACE ACTIVITY AND COLLOID-CHEMICAL PROPERTIES OF NEW BIOLOGICAL SURFACE-ACTIVE SUBSTANCES (British Journal of Global Ecology and Sustainable Development, 2023)
The purpose of this work was obtaining of new biological surface-active substances and establishing correlations between their surface activity and colloid-chemical properties. The well-known methods for separation and determining the surface activity and colloid-chemical properties of biosurfactants were used in the work. The new biological surfactants were isolated by acid precipitation and purified by solvent extraction. The surface activity and foaming ability of the obtained new biosurfactants in aqueous solutions were studied depending on concentration and temperature of the system. The obtained results showed that with an increase jf the concentration of surfactants in water solutions, the surface activity of new biosurfactants increases. The analysis of results showed a good correlation between the foam forming ability and the surface activity of the studied biosurfactants. Based on the studies it was established that the stability of foams is significantly determined by the interaction of surfactant molecules in the monolayer.